2014
DOI: 10.1039/c4ob01251h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conformational rigidity on the stereoselectivity of nucleophilic additions to five-membered ring bicyclic oxocarbenium ion intermediates

Abstract: Nucleophilic substitution reactions of five-membered ring acetals bearing fused rings reveal that subtle changes in the structure of the fused ring can exert dramatic influences on selectivity. If the fused ring did not constrain the five-membered ring undergoing substitution, selectivity was comparable to what was observed for an unconstrained system (≥92% diastereoselectivity, favoring the product of inside attack on the oxocarbenium ion). If the ring were more constrained by including at least one oxygen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 56 publications
(149 reference statements)
1
18
0
Order By: Relevance
“…While the cyclopentane-derived acetal trans-5 ionized nearly four times slower than the sterically equivalent alkyl acetal 12, the cyclooctane-derived acetal trans-8 ionized over 20 times faster than the alkyl acetal. The trend of increasing rate as more carbon atoms are introduced to the tethering ring is consistent with the idea that the more flexible ring 44,45 allows the alkoxy group to approach the acetal undergoing substitution more closely, leading to accelerated hydrolysis, as observed for galactosides compared to glucosides ( Figure 1). The nearly three-fold slower reaction of the cissubstituted acetal cis-6 with a six-membered ring compared to its trans-substituted analogue trans-6 may reflect minor differences in the energies of transition states resembling fused rings (trans-hydrindane being slightly less strained than the cis isomer 46,47 ).…”
Section: ■ Results and Discussionsupporting
confidence: 80%
“…While the cyclopentane-derived acetal trans-5 ionized nearly four times slower than the sterically equivalent alkyl acetal 12, the cyclooctane-derived acetal trans-8 ionized over 20 times faster than the alkyl acetal. The trend of increasing rate as more carbon atoms are introduced to the tethering ring is consistent with the idea that the more flexible ring 44,45 allows the alkoxy group to approach the acetal undergoing substitution more closely, leading to accelerated hydrolysis, as observed for galactosides compared to glucosides ( Figure 1). The nearly three-fold slower reaction of the cissubstituted acetal cis-6 with a six-membered ring compared to its trans-substituted analogue trans-6 may reflect minor differences in the energies of transition states resembling fused rings (trans-hydrindane being slightly less strained than the cis isomer 46,47 ).…”
Section: ■ Results and Discussionsupporting
confidence: 80%
“…All structures studied during the DFT investigation of the anisole reaction mechanism were optimized with the Gaussian 09 program package . Previously reported studies on the allylation reaction of five-membered ring oxocarbenium ions, by Woerpel and co-workers, showed that the use of B3LYP could results in difficulties in locating the transitions states when allyltrimethylsilane was involved in the reaction, thus suggesting the use of M06-2X . Considering the different types of reactants involved, we decided to use the more parametrized B3LYP functional anyway, by specifying a differentiated basis set .…”
Section: Methodsmentioning
confidence: 99%
“…When a cyclic protecting group spans the 3- and 5-positions selectivity is a function of the size of the appended ring and its nature. 126,127…”
Section: Facial Selectivity Of Nucleophilic Attack On Putative Glycmentioning
confidence: 99%